Tingkat Literasi Keuangan Petani Padi Sawah terhadap Keputusan Pengambilan Kredit di Kecamatan Tilongkabila, Kabupaten Bone Bolango, Gorontalo - Tengkeran, Nurul Amelia R.; Bakari, Yuliana; Baruwadi, Mahludin H.; Hippy, Mohammad Zubair (Journal Galung Tropika, 2025)
Rice is a mainstay commodity in Bone Bolango Regency, Tilongkabila District. Fluctuations in agricultural commodity prices, including rice prices, create price uncertainty at the marketing level that can hamper rice farming internally and externally. One of the obstacles is capital, which, if not addressed comprehensively, will ensure the sustainability of the farming business. The rice farming industry is capital intensive, from input financing to the labor required. Most rice farmers cannot cover the high cost of farming if they only rely on their capital, so literacy skills are needed. This study aims to analyze rice farmers' financial literacy level and its influence on credit decisions. The number of samples in this study was 120 farmers using a non-probability sampling technique, accidental sampling, and the Harry King Nomogram. The results showed that the financial literacy level of rice farmers in Tilongkabila District is in the moderate category, with a percentage score of 68%. Meanwhile, the analysis results with Binary Logistic Regression show that the variables Financial Knowledge, Financial Behavior, Financial Attitude and Financial Experience have a negative and insignificant influence on credit decisions.